A Closed-Loop Alarm Management System for Hazardous Chemical Enterprises Based on Personnel Positioning Data - Yang, Haoran (Scientific Journal of Technology, 2026)
Personnel positioning platforms are widely used in hazardous chemical enterprises, but location output alone is still not a safety-control process. In many plant deployments, frequent location snapshots sit apart from rule configuration, alarm archives, response traces, and later review. The scheme uses the output of an existing positioning engine to support closed-loop alarm management. The localization algorithm is left unchanged. The main work is to convert location results into normalized events, electronic geofences, reusable alarm strategies, responsibility-delivery ledgers, response logs, and loop indicators that can be audited. The architecture includes the positioning platform, a business-processing layer, and a front-end management interface. The service layer unifies snapshots, binds tags to personnel objects, performs floor-aware geofence judgment, creates alarm events, records delivery and response evidence, and calculates loop processing time. Anonymized operational samples from alarm, delivery, response, and positioning tables are used for limited verification. The checks cover event-chain completeness, timestamp consistency, calculable closure duration, timeout identification, and ledger consistency. The result is a workflow for turning personnel positioning data into traceable safety-management actions in hazardous chemical plant scenarios, while broader efficiency evaluation requires larger sample disclosure.